Comparative study of application methods of biofertilizer for growth enhancement of cereals - Mujeeb, Fakhar; Ali, Abid; Qureshi, Muhammad Amjad; Sarwar, Ghulam; Ali, Muhammad Asif; Mahmood, Khalid; Javed, Hina; Rafique, Munazza; Ijaz, Fraza; Ehsan, Shabana (Journal of Pure and Applied Agriculture, 2023)
The nutrient management plays a vital role in consistent agricultural production and maintenance of soil fertility. Due to price hikes, chemical fertilizers are going beyond the affordability of poor farming communities. Hence, agricultural scientists and farming communities are switching to other judicious and environment friendly substitutes. Use of biofertilizers is becoming popular day by day. Nevertheless, its popularity has to face some challenges like application methods. Farmers in Punjab have the practice to apply the biofertilizers on the growing crops either through spray or flooding or with irrigation water. This glass-house trial was designed to evaluate a more effective and efficient way for the application of biofertilizer to the cereals. Wheat and rice cereals were used as test crops. Three biofertilizer application methods viz. seed coating, flooding and foliar spray were tested employing eight treatments and following Completely Randomized Design (CRD) with three repeats. At maturity, yield data regarding wheat and rice crops were recorded. Statistical analysis of the data revealed that better yield was obtained in all treatments supplied with biofertilizer inoculation along with recommended dose of chemical fertilizers compared to the control with no inoculum application but only chemical fertilizer application. Moreover, integration of individual inoculum application techniques proved better than their individual application. © 2022 Department of Agricultural Sciences, AIOU